ISLAMIC BANKING AND INVESTMENT FINANCING: A CASE OF ISLAMIC BANKING IN KENYA - Abubakar, Abbas Said; Aduda, Dr. Josiah (International Journal of Finance, 2017)
Purpose: The purpose of this study was to establish the effect of Islamic banking on investment financing in Islamic banks in Kenya. Methodology: This study employed descriptive survey design. The population of this research consisted of 8 commercial banks offering Shariah compliant products. The study used secondary data for the period 2009 to 2012. Data was analyzed using Statistical Package for Social Sciences (SPSS) and results were presented in frequency tables and figures. The data was then analyzed in terms of descriptive statistics like frequencies, means and percentages. Results: The study findings indicated that there were various Islamic banking products that Islamic banks used to finance their investments. This included motor vehicle financing, mortgage financing, asset financing, real estate financing, trade financing and SME financing. The study also indicated that there were various modes of financing used by Islamic banking such as profit and loss sharing, Ijara and murahaba. Regression results revealed that motor vehicle financing was statistically significant in explaining loans advanced to customers in Islamic banks. However mortgage financing, asset financing, real estate financing, trade financing and SME financing were not statistically significant in explaining loans advanced to customers in Islamic banks but they were positively correlated. Unique contribution to theory, practice and policy: The study recommends that the management of the banks to get well equipped and competent employees on Islamic banking products as most Islamic banks are currently managed by people who have been educated and trained in the conventional banking system. Thus, more time may be required for the unique characteristics of Islamic financial instruments to be completely accepted and understood by both bank personnel and customers. It is also recommended that the terms and conditions of acquiring a loan be made more appealing and considerate for more investors to approach the banks for assistance as the Shari`ah restricts the type of businesses for which Islamic banks can provide financing.